Multi-layer plain bearing element
A copper-based alloy with controlled sulfur and additive elements forms sulfide precipitates, addressing porosity and grain coarsening issues in lead-free bearings, enhancing castability and tribological performance.
Patent Information
- Application Number
- JP2020082239
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-05-07
- Filing Date
- 2020-05-07
- Publication Date
- 2024-12-26
- Estimated Expiration
- 2040-05-07
AI Technical Summary
Existing lead-free copper alloys used in multilayer sliding bearings face issues such as porosity, grain coarsening, and reduced mechanical properties due to sulfur additions, which affect casting quality and tribological performance.
A copper-based alloy with controlled sulfur content (0.1% to 3% by weight) and specific additives like iron, phosphorus, and other elements (0.01% to 4% by weight) forms sulfide precipitates that act as crystallization nuclei, improving castability and mechanical properties, reducing grain coarsening, and enhancing tribological performance.
The alloy achieves improved castability, reduced porosity, enhanced mechanical properties, and superior tribological performance, allowing for better coating adherence and increased service life of the bearings.
Smart Images

Figure 0007606822000010 
Figure 0007606822000011 
Figure 0007606822000012
Abstract
Description
[Technical field]
[0001] The invention relates to a multi-layer plain bearing made of a composite material, which has a supporting metal layer, a further layer, in particular a sliding layer, and possibly an intermediate layer between the supporting metal layer and the further layer, the further layer being formed from a lead-free copper-based casting alloy, in which sulfide-containing precipitates are contained. [Background technology]
[0002] Lead bronze has been used for a long time in multi-layer plain bearings made of composite material with a supporting metal layer and a sliding layer for the automotive industry, because it has good tribological behavior due to lead deposits. Furthermore, its production by casting technology is very robust from the viewpoint of process technology, because metallurgical microsegregation and the associated void formation are prevented or compensated for by lead. However, for environmental reasons, leaded bronze must be avoided. For this purpose, various approaches to the alloying of the sliding layer already exist in the prior art. For example, in the case of casting alloys based on brass or bronze, alloying additives such as chromium, manganese, zirconium or aluminum are used to improve the friction properties, in particular to reduce the tendency to seize.
[0003] The use of sulfur in copper alloys has already been described in several documents, for example in WO 2010 / 137483, US 2012082588, US 2012 / 121455, DE 20 2016 101 661 or WO 2007 / 126006. Sulfur is primarily used to improve the cutting properties of red brass alloys (Rotgusslegierungen, red brass) (CuSnZn-matrix). Furthermore, improved tribological properties are reported in said documents. However, the fundamental property of the aforementioned red brass alloys, also in combination with further alloying elements, of having a wide solidification range, hampers their use in several respects. In particular the casting quality is an issue. The wide solidification range, for example of about 150 ° C. in the case of the alloy CuSn7Zn2, is the cause of significant shrinkage porosity, which in turn leads to defects in the material, especially when used as a casting alloy. At low zinc contents, the density difference between the liquid and solid phases is also greater. This further intensifies the problem of shrinkage porosity. Even when used as a wrought alloy, the porosity of the casting can only be partially closed through the high degree of deformation. In both cases, the correspondingly increased quality problems, the resulting increased inspection effort, and the correspondingly higher waste amount as a further consequence must be taken into account. The results of subsequent coating processes, which are becoming increasingly important, such as galvanic or polymer coatings, are also impaired. If lead-free copper alloys are to replace today's lead bronzes, which have outstanding tribological properties, such coatings will become increasingly important, for example, especially when used as plain bearing materials.
[0004] Furthermore, when such alloys are advantageously used as wrought alloys due to the occurrence of porosity, they are usually annealed after the deformation process so as to recrystallize, which reduces the internal stresses and the resulting high material hardness or increases the small residual deformation potential again after deformation. Most alloying elements which increase the stiffness or improve the corrosion resistance have the disadvantage of increasing the recrystallization temperature. The sulfur additions mentioned for the desired properties of the alloy according to the invention have a comparable effect. At the high annealing temperatures which are required hereby, copper alloys tend to coarsen grains, especially in combination with long processing times. Coarsening grains weaken the matrix material. In particular, in the case of materials which are distinguished by a high degree of work hardening, this leads to the problem that the grains are coarsened or that recrystallization is insufficient and residual dendrites remain. This has the same adverse effect on the mechanical properties of the material as an excessively coarse structure. Furthermore, at high annealing temperatures, the stiffness of the steel support layer usually decreases to the value in the annealed state. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2010 / 137483 [Patent Document 2] US Patent Publication No. 2012082588 [Patent Document 3] US Patent Application Publication No. 2012 / 121455 [Patent Document 4] German Utility Model No. 20 2016 101 661 [Patent Document 5] International Publication No. 2007 / 126006 Summary of the Invention [Problem to be solved by the invention]
[0006] The object of the present invention is to provide a plain bearing element having a lead-free, sulfur-containing casting alloy based on copper as a further layer, in which the partially adverse effects of sulfur on the alloy are reduced. [Means for solving the problem]
[0007] The subject of the present invention is a multilayer plain bearing element as mentioned at the beginning, in which the copper-based alloy contains 0.1% to 3% by weight of sulfur, 0.01% to 4% by weight of iron, 0% by weight, in particular 0.001% to 2% by weight of phosphorus and a total of 0.1% to 49% by weight of at least one element from a first group consisting of zinc, tin, aluminium, manganese, nickel, silicon, chromium and indium, in which the proportion of zinc is 0% to 45% by weight, the proportion of tin is 0% to 40% by weight, the proportion of aluminium is 0% to 15% by weight, the proportion of manganese is 0% to 10% by weight, the proportion of nickel is 0% to 10% by weight, the proportion of silicon is 0% to 10% by weight and the proportion of chromium is 0% to 10% by weight. The problem is solved by the fact that the alloy contains at least one element from the first group, in which the ratio of silver, magnesium, cobalt, titanium, zirconium, arsenic, lithium, yttrium, calcium, vanadium, molybdenum, tungsten, antimony, selenium, tellurium, bismuth, niobium, and palladium is 0% by weight to 1.5% by weight, respectively, and at least one element from the second group consisting of silver, magnesium, cobalt, titanium, zirconium, arsenic, lithium, yttrium, calcium, vanadium, molybdenum, tungsten, antimony, selenium, tellurium, bismuth, niobium, and palladium, the total ratio of the elements of the second group being 0% by weight to 2% by weight, and the remainder up to 100% by weight is formed by copper and impurities derived from the production of the elements. Effect of the Invention
[0008] The advantage here is that the low-alloy copper-based alloys formed therefrom are distinguished by good castability due to the addition of sulfur. This allows the alloys to be used in plain bearings, which are otherwise only suitable to a limited extent. Furthermore, the copper sulfides formed by sulfur act as crystallization nuclei during solidification and thus have a grain-refining effect. Furthermore, such materials can be worked without additional coatings. Furthermore, the machinability can be improved, since the sulfides act as chip breakers. This improved machinability leads to improved surface quality with reduced roughness values and reduced defect points. As a further consequence, this can have a favorable effect on the quality of many coatings, such as galvanic coatings, PCD or polymer coatings. In other words, this improves the coatability of the copper-based alloys.
[0009] Copper-based alloys contain sulfur and a combination of small amounts of iron and phosphorus. Phosphorus is primarily used as a deoxidizer, as in the melt metallurgical processing of the material. The excess phosphorus in the copper-based alloy combined with the iron addition allows a grain-refining effect to be achieved. This allows a uniform and fine distribution of intermetallic phases (mainly sulfide phases) with copper and the remaining alloying elements to be achieved. The combination of iron and phosphorus allows iron phosphides to form already in the melt. Not only does this allow a portion of the phosphorus, which is detrimental to the bond with the steel substrate, to be bound, but these intermetallic phases also reduce the tendency to grain coarsening during the recrystallization annealing process. This allows the mechanical properties of the copper-based alloy to be improved. Furthermore, these iron phosphide phases allow the copper-based alloy to have a high heterogeneity due to its high hardness. This has a favorable effect on the tribological properties.
[0010] The tendency of lead-free copper-based bearing alloys to seize can be reduced by the intermetallic FeS phase that occurs in addition to copper sulfides. The tribological behavior that can be achieved with copper-based alloys can be seen in the combination of copper sulfides (mainly CuS) and iron sulfide (FeS).
[0011] The addition of sulfur to copper-based alloys makes it possible to increase the recrystallization temperature of copper, reduce the susceptibility to the so-called hydrogen disease of copper, improve the machinability by improving chip breaking with the formation of short breaking chips, the wear inhibition effect on the machining tools and thus an increased service life of the tools, and the resulting surface quality.
[0012] The addition of iron allows the distribution of sulfur precipitates to be improved through a grain-refining effect. A fine distribution and the formation of iron sulfides allow the tribological properties to be increased. An addition of more than 5% by weight of iron, in addition to increasing the liquidus temperature, has the effect of significantly increasing the hardness and, as a result, worsening the deformability. With the addition of small amounts of phosphorus, iron phosphide (Fe2P) is formed directly in the melt, which is desirable here, as opposed to in the bonding zone with the steel. On the one hand, said phase allows the grain growth to be limited during the annealing treatment, without itself having a detrimental effect on the recrystallization ability, which significantly facilitates the process implementation, especially during such hot treatments, and on the other hand, the incorporation of iron phosphide into the copper matrix has a favorable effect on the wear resistance of such alloys.
[0013] Due to its affinity for oxygen and hydrogen, lithium can be used as a deoxidizer in copper alloys and to remove hydrogen. Lithium can thus at least largely replace the phosphorus content, which makes it possible to avoid the aforementioned problems in composite casting processes, for example for joining bearing alloys to a steel substrate, due to an excessively high phosphorus content and the resulting brittle phases. The brittle phases form exactly in the bonding zone of the material composite and affect the bond strength depending on their development until complete separation. Lithium as a deoxidizer never forms intermetallic phases with iron from the steel substrate, even when added in larger amounts. By using lithium, the phosphorus addition can be reduced to a minimum or even omitted completely, which also prevents the formation of brittle phases or allows the targeted adjustment of a low phosphorus content. The consumed lithium forms a low-density liquid slag, which can then float. This makes it possible to protect the melt from further oxygen ingress and subsequent combustion of the alloying elements.
[0014] It should be mentioned here that the amount of lithium consumed for deoxidizing the melt is of course adapted to the oxygen ratio in the melt, so that the skilled person can add a corresponding excess of lithium if necessary to accommodate the actual oxygen ratio.
[0015] When making compositions corresponding to sulfur-containing red copper alloys, lithium can be used as a grain refiner instead of zirconium or calcium (both of which have a desulfurizing effect). Zirconium also acts as a grain refiner, but reacts with sulfur, thereby reducing its effect.
[0016] The addition of yttrium can improve the corrosion resistance of lead-free copper-based alloys. A quantity ratio of 0.1% by weight reduces the weight gain due to oxidation by approximately 50%. The reduced tendency to oxidize can stabilize the bond of the polymer coating with the bearing material during operation of the plain bearing and thus increase the operating reliability.
[0017] To increase the tribologically effective phase, selenium and / or tellurium can be added.
[0018] Indium has a high solubility in copper (>10% by weight). It can form intermetallic phases and can be used for precipitation hardening. The advantage of indium is that the bearing material has an improved ability to adapt after quenching until the copper-based alloy reaches its final hardness at elevated temperatures (e.g. during operation in plain bearings) through a long-term age-hardening effect.
[0019] The advantageously low tin content makes it possible to avoid a significant increase in hardness of the copper-based alloy. Within the range of amounts mentioned above, the sulfide distribution in the alloy can be more favorably influenced. The reduction of the tin content leads to alloys in which the grain structure of the structure is less pronounced and larger grains are generated.
[0020] Depending on the zinc content, a better defined spherical shape of the precipitated sulfides can be achieved.
[0021] The above proportions of silicon may be advantageous with regard to castability and deoxidization of the alloy.
[0022] The addition of aluminum in the copper-based alloy avoids the tendency towards corrosion at high temperatures. In the above amount ratios, the formation of β mixed crystals is avoided with a high degree of certainty.
[0023] Manganese can increase the heat resistance, and improved recovery of the corrosion protection layer can be achieved with manganese-containing alloys.
[0024] Nickel can form nickel sulfides with sulfur, which can increase the overall phase number. In addition, nickel can improve the corrosion stability of copper-based alloys. The elastic modulus of Cu-Ni alloys increases linearly with nickel addition.
[0025] Chromium can improve the recrystallization temperature and heat resistance of copper-based alloys.
[0026] According to an advantageous embodiment of the multilayer plain bearing element, the copper-based alloy of the further layer may contain zinc or tin. By avoiding the combination of both elements in the copper-based alloy, the casting properties of the alloy can be significantly improved, since this allows the solidification range of the copper-based alloy to be narrowed.
[0027] In order to further improve said properties of the copper-based alloy, at least one of the following embodiments of the present invention may be provided: the total proportion of elements from said first group consisting of zinc, tin, aluminium, manganese, nickel, silicon and chromium is between 0.5% and 15% by weight, and / or - the copper-based alloy of the further layer contains between 0.01% and 5% by weight of zinc, and / or - the copper-based alloy of the further layer contains between 0.01% and 10% by weight of tin, and / or - the copper-based alloy of the further layer contains between 0.01% and 7.5% by weight of aluminium, and / or - the copper-based alloy of the further layer contains between 0.01% and 5% by weight of manganese, and / or the copper-based alloy of the further layer contains 0.01% to 5% by weight, in particular 0.01% to 2% by weight, of nickel, and / or the copper-based alloy of the further layer contains 0.01% to 7% by weight, in particular 0.01% to 3% by weight, of silicon, and / or the copper-based alloy of the further layer contains 0.01% to 1.5% by weight, in particular 0.01% to 1% by weight, of chromium, and / or - the copper-based alloy of the further layer contains between 0.3% and 0.8% by weight of sulfur, and / or - the copper-based alloy of the further layer contains between 0.01% and 0.1% by weight of phosphorus, and / or the copper-based alloy of the further layer contains between 0.3% and 1.5% by weight of iron.
[0028] According to another embodiment of the multilayer plain bearing element, the copper-based alloy of the further layer may additionally contain 0.001% to 1.5% by weight, in particular 0.001% to 1% by weight, of boron. This allows a denser structure of the grain boundaries to be obtained. The copper alloy thereby has improved strength (increased grain boundary strength) and ductility. Furthermore, the alloy shows a reduced risk of cracking. This allows the structure in the further layer to have a higher crack resistance. Furthermore, boron is also favorable with regard to the deoxidization of the melt and, in some cases, acts together with iron as a grain refiner.
[0029] According to another embodiment, the sulfide-containing precipitates may be present homogeneously distributed within the entire further layer, so that the further layer has substantially the same properties, i.e. across the entire cross section.
[0030] However, according to another embodiment of the multilayer plain bearing element, the sulfide-containing precipitates can also be formed only within a partial layer of the copper-based alloy of the further layer, so that the layer itself can be endowed with a broader spectrum of properties, and the multilayer plain bearing element can possibly be constructed more simply by reducing the number of layers.
[0031] According to one embodiment for this, the partial layers may have a layer thickness that is 5% to 85% of the total layer thickness of the further layers. If the ratio of the layer thickness of the partial layers is less than 5% of the total layer thickness, the further layers can no longer fulfill their role as further layers, in particular as sliding layers, of the multilayer plain bearing element to the desired extent. However, the further layers can still have the properties of a run-in layer in that case. In contrast, for layer thicknesses that are more than 85% of the total layer thickness, the effort required to produce the partial layers outweighs the benefits of reducing the number of individual layers.
[0032] The added sulfur reacts with other components of the copper-based alloy to form sulfides. According to another embodiment of the invention, the sulfide-containing precipitates may consist of at least 50% by area of a mixture of copper sulfide and iron sulfide, which improves the self-lubricating behavior of the copper-based alloy.
[0033] To further improve this effect, according to another embodiment of the multilayer plain bearing element, the proportion of copper sulfide in the mixture of copper sulfide and iron sulfide may be at least 60% by area.
[0034] For a better understanding of the invention, the invention will now be described in more detail with reference to the following drawings.
[0035] The figures are each highly simplified schematic diagrams. [Brief description of the drawings]
[0036] [Figure 1] FIG. 1 is a side view of a multi-layer plain bearing element. [Diagram 2] FIG. 2 is a partial side view in section of the sliding layer of one embodiment of a multi-layer plain bearing element. [Diagram 3] FIG. 3 is a partial side view in section of the sliding layer of another embodiment of a multilayer plain bearing element. [Figure 4] FIG. 4 is a partial side view in section of the sliding layer of another embodiment of a multilayer plain bearing element. [Diagram 5] FIG. 5 is a partial side view in section of the sliding layer of one embodiment of a multi-layer plain bearing element. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0037] It should be noted at the outset that in the embodiments described as different, the same parts are given the same reference numbers or component numbers. The disclosure contained in the entire description can be transferred accordingly to the same parts having the same reference numbers or component numbers. Also, the descriptions of selected positions in the description, such as above, below, side, etc., refer to the figures directly described and illustrated, and when the positions are changed, these position descriptions can be transferred accordingly to the new positions.
[0038] FIG. 1 shows a multi-layer plain bearing element 1 made of composite material, in particular a radial plain bearing element, in a side view.
[0039] The multilayer plain bearing element 1 is provided in particular for use in combustion engines or for supporting shafts, but it can also be used for other applications, for example in wind power plants, in particular in wind power plant transmissions, for example in or as coverings for planetary gear pins in the planetary gear bearing area, as inner coverings for gears (also for supporting gears), as industrial plain bearings in compressors, steam turbines and gas turbines or as part of plain bearings for rail vehicles, etc.
[0040] The multilayer plain bearing element 1 comprises a plain bearing element body 2. The plain bearing element body 2 comprises a supporting metal layer 3 and a further layer 4 arranged thereon or consists of the supporting metal layer 3 and the further layer 4 connected to the supporting metal layer.
[0041] As can be seen from figure 1 indicated by dashed lines, the plain bearing element body 2 can also have one or more additional layers, for example a bearing metal layer 5 arranged between said further layer 4 and the supporting metal layer 3 and / or a run-in layer 6 on said further layer 4. At least one diffusion barrier layer and / or at least one bonding layer may be arranged between at least two of the layers of the multilayer plain bearing element 1.
[0042] The basic structure of such a type of multilayer plain bearing element 1 is known in the prior art, so reference is made to the relevant literature for details of the layer structure.
[0043] Likewise, the materials used, which may constitute the supporting metal layer 3, the bearing metal layer 5, the running-in layer 6, the at least one diffusion barrier layer and the at least one bonding layer, are also known in the prior art, and reference is made in this regard to the relevant literature. By way of example, the supporting metal layer 3 may be made of steel, the bearing metal layer 5 may be made of a copper alloy having 5% by weight tin and the balance copper, the running-in layer may be made of a synthetic polymer or a PVD coating containing tin, lead or bismuth or at least one additive, and the diffusion barrier layer may be made of copper or nickel, for example.
[0044] The half-shell-shaped multilayer plain bearing element 1 together with at least one further plain bearing element 7 (depending on the constructional design, two or more further plain bearing elements 7 may also be provided) forms a plain bearing 8. The plain bearing element which is located underneath in the assembled state is advantageously formed by a multilayer plain bearing element 1 according to the invention. However, at least one of the at least one further plain bearing element 7 can also be formed by a multilayer plain bearing element 1 or the entire plain bearing 8 can be formed from at least two multilayer plain bearing elements 1 according to the invention.
[0045] Furthermore, the plain bearing element 1 can also be configured as a plain bearing bush, as indicated by the dashed lines in Fig. 1. In such a case, the multi-layer plain bearing element 1 is at the same time a plain bearing 8.
[0046] It is furthermore possible for the further layer 4 to directly form a coating, for example a coating on the radial inside of a connecting rod eye. In this case, the structural part to be coated, i.e. for example a connecting rod, forms the supporting metal layer 3.
[0047] Furthermore, the multilayer plain bearing element 1 or the plain bearing 8 may also be designed in the form of a thrust washer, a collar bearing, etc.
[0048] The further layer 4 is in particular formed as a sliding layer 9. For this purpose, a first embodiment of such a sliding layer 9 is shown in FIG.
[0049] The sliding layer 9 consists of a casting alloy consisting of a copper-based alloy.
[0050] The copper-based alloy comprises, in addition to copper, sulfur, iron and phosphorus, at least one element from a first group consisting of zinc, tin, aluminum, manganese, nickel, silicon, chromium and indium in a total amount of 0.1% to 49% by weight, and at least one element from a second group consisting of silver, magnesium, cobalt, titanium, zirconium, arsenic, lithium, yttrium, calcium, vanadium, molybdenum, tungsten, antimony, selenium, tellurium, bismuth, niobium and palladium, the total proportion of the elements of said second group being between 0% and 2% by weight.
[0051] Optionally, the copper-based alloy of said further layer 4 may additionally contain boron.
[0052] The copper-based alloy is lead-free, which means that it may contain up to 0.1% lead by weight.
[0053] The primary effects of the individual elements in copper-based alloys are known in the art and reference is made thereto, and further reference is made to the above discussion of the effects of alloying elements.
[0054] Possible ratios of individual elements in copper-based alloys are summarized in Table 1. The percentages for ratios in Table 1, as well as throughout the specification, are to be understood as weight percent, unless expressly stated otherwise.
[0055] In any copper-based alloy, copper forms the balance to 100% by weight, excluding unavoidable impurities.
[0056] [Table 1-1] [Table 1-2]
[0057] The indications of amount ranges in Table 1 must be understood as if the respective limit ranges and intermediate ranges are also claimed by said indications. For example, the proportion of S may be 0.1-3, 0.2-1.5, 0.3-0.8, 0.1-0.2, 0.1-1.5, 0.1-0.3, 0.1-0.8, 0.2-0.3, 0.2-0.8, 0.3-3, 0.3-1.5, 0.8-3, and 0.8-1.5, respectively, in weight percent. The same applies to the further elements in Table 1.
[0058] The total proportion of elements from a first group including or consisting of zinc, tin, aluminum, manganese, nickel, silicon, chromium is preferably at most 7% by weight, in particular at most 5% by weight, for example the total proportion of elements from the first group may be between 0.5% and 15% by weight.
[0059] It is further advantageous if tin and zinc are not contained together in the copper-based alloy, ie if the copper-based alloy contains tin or zinc.
[0060] As can be seen from Figure 2, sulfide-containing precipitates 10 are contained within the sliding layer 9. Such sulfide-containing precipitates 10 are formed by reaction of sulfur with at least one metal alloying component of the copper-based alloy. Mixed sulfides are also possible.
[0061] As will become apparent from the method described below, the sulfide-containing precipitates 10 of the copper-based alloy are not added as such, even though they may be included within the scope of the present invention; these precipitates 10 are produced from at least one alloy component as a result of reduction reactions in the melt during the manufacture of the alloy.
[0062] Advantageously, the proportion of sulfide-containing precipitates 10 in the copper-based alloy is between 1% and 20% by area, in particular between 2% and 15% by area. If the proportion exceeds 24% by area, the sulfur content may become undesirably noticeable at the grain boundaries. If the proportion is lower than 1% by area, the effect is still observed, but its magnitude is not satisfactory. The indications of area percentages are in each case relative to the total area of the longitudinal cross section of the sliding layer 9.
[0063] The sliding layer 9 has a total layer thickness 11. The total layer thickness 11 is in particular between 100 μm and 2500 μm, preferably between 150 μm and 700 μm.
[0064] As can be seen from FIG. 2, in this embodiment, the sulfide-containing precipitates 10 are advantageously arranged in a homogeneously distributed manner throughout the entire layer thickness 11 of the sliding layer 9 and thus throughout the entire sliding layer 9, i.e. within the entire volume of the sliding layer.
[0065] The expression "homogeneous" means that the difference in the number of sulfide-containing precipitates 10 in each of two different volume regions of the sliding layer 9 is less than 12%, in particular less than 9%. As a reference value with 100%, the number of sulfide-containing precipitates 10 in one volume region of the sliding layer 9 is taken. This is calculated from the total number of precipitates 10 in the entire volume of the sliding layer 9 divided by the number of volume regions that the total volume contains.
[0066] However, the arrangement or formation of the sulfide-containing precipitates 10 can also be limited to only the region inside the partial layer 12 of the sliding layer 9, as is evident from FIG. 3. The sulfide-containing precipitates 10 are arranged inside such a partial layer 12, in particular exclusively inside. Within such a partial layer 12, the sulfide-containing precipitates 10 are preferably also arranged in a homogeneously distributed manner. The concept "homogeneous" is to be understood in the sense of the above definition, in which "sliding layer" is replaced by "partial layer".
[0067] Furthermore, according to one embodiment, the layer thickness 13 of the partial layer 12 may be 5% to 85%, in particular 10% to 50%, of the total layer thickness 11 of said further layer 4, ie in this embodiment the sliding layer 9.
[0068] The partial layer 12 is preferably formed on one side of the sliding layer 9 and thus preferably forms a surface 14, in particular the sliding surface, of the multilayer plain bearing element 1.
[0069] However, as shown in Fig. 4 for the partial layer 12, it is also possible that the number of sulfide-containing precipitates 10 decreases from the surface 14 of the copper-based alloy of the sliding layer 9 towards the supporting metal layer 3. Such a gradient may be formed throughout the sliding layer 9, i.e. not only in the partial layer 12. The sulfide-containing precipitates 10 are in this case present within the entire volume of the sliding layer 9, in the sense of Fig. 2.
[0070] It should be noted that the figures each show an independent embodiment of a possibly multi-layer plain bearing element 1. Identical parts are designated by reference or component signs. In order to avoid unnecessary repetition, a detailed description of the entire figures is suggested or reference is made to the drawings.
[0071] By reducing the number of sulfide-containing precipitates 10 in the sliding layer 9 or in a sublayer 12 of the sliding layer 9 toward the supporting metal layer 3, the hardness gradient in the sliding layer 9 can be adjusted.
[0072] It is also possible for the number of sulfide-containing precipitates 10 in the sliding layer 9 or in a partial layer 12 of the sliding layer 9 to increase gradually or to vary roughly from the surface 14 of the copper-based alloy of the sliding layer 9 towards the supporting metal layer 3.
[0073] Roughly speaking, the sulfide-containing precipitate 10 has a maximum grain size 15 (FIGS. 2 and 3) of up to 60 μm, particularly 0.1 μm to 30 μm. The maximum grain size 15 is preferably 10 μm to 25 μm. The maximum grain size 15 refers to the largest dimension that a grain has.
[0074] The grain size of the remaining structure may be between 2 μm and 500 μm, in particular between 2 μm and 40 μm. Advantageously, larger grains occur only in the bonding zone between the sliding layer 9 and the layer of the multilayer plain bearing element 1 arranged immediately below. In the particular case of dendritic cast structures, the grain size can also correspond to the entire layer thickness.
[0075] It is possible for the grain size 15 of the sulfide-containing precipitates 10 to remain approximately constant over the entire volume of the sliding layer 9, ie the maximum grain size of the precipitates 10 to differ by no more than 20%, in particular no more than 15%.
[0076] On the other hand, according to a further embodiment of the multilayer plain bearing element 1, as shown in Figure 5, the maximum grain size 15 of the sulfide-containing precipitates 10 may gradually decrease from the surface 14 of the copper-based alloy towards the supporting metal layer 3. The grain size 15 of the sulfide-containing precipitates 10 may be reduced by a value selected from the range of 0.1% to 80%, in particular from the range of 0.1% to 70%, based on the grain size 15 of the precipitates 10 in the region of the surface 14.
[0077] However, the maximum grain size 15 of the sulfide-containing precipitates 10 can also be gradually increased or even varied from the surface 14 of the copper-based alloy towards the supporting metal layer 3. The grain size 15 of the sulfide-containing precipitates 10 can be increased by an amount selected from the range of 0.1% to 80%, in particular from the range of 0.1% to 70%, based on the grain size 15 of the sulfide-containing precipitates 10 in the region of the surface 14.
[0078] The external shape of the sulfide-containing precipitate 10 may be at least approximately spherical, at least approximately elliptical or ovoid, bulbous, rod-like (i.e., elongated), at least approximately cubic, etc., or may be completely irregular. Advantageously, the sulfide-containing precipitate 10 is formed as at least approximately circular, or at least approximately spherical, or at least approximately elliptical.
[0079] As already mentioned, the precipitate 10 has a sulfide nature. The sulfide-containing precipitate 10 may consist mainly of copper sulfide and / or iron sulfide. The proportion of such mixtures in the total proportion of sulfides is at least 50% by area, in particular at least 70% by area, preferably at least 80% by area. Besides such sulfides, as already mentioned above, further sulfides are also present in the copper-based alloy, for example zinc sulfide.
[0080] The zinc sulfide may be formed within at least one discontinuous region within the copper sulfide particle. One to five such discontinuous regions may be formed within the copper sulfide particle. In other words, the zinc sulfide may be contained in a non-uniformly distributed state within the copper sulfide particle.
[0081] The alloy may also contain a mixture of copper sulfide and iron sulfide. Within such a mixture of copper sulfide and iron sulfide, the proportion of copper sulfide may be at least 60% by area, in particular at least 75% by area.
[0082] In order to achieve the finest possible distribution of the sulfide phase (sulfide-containing precipitates 10) in the further layer 4, which allows better utilization of the sulfur addition effect, a fine matrix structure should be formed. This can be achieved on the one hand via high cooling rates and on the other hand via metallurgical grain refinement.
[0083] In the case of sulfur-containing alloys, it has been found that many of the grain-refining alloying elements additionally have a high affinity for sulfur, which leads to the formation of some undesirable compounds that then tend to slage. In the case of copper alloys, particular mention must be made of zirconium, which can act as a very good grain refiner, but also has a strong desulfurization effect. A further element for grain refinement in copper is, for example, calcium, which is, however, known for its desulfurization effect in the steel industry. In principle, desulfurization can be prevented via the sulfur ratio, the temperature behavior and the time of addition.
[0084] Many grain refiners known for copper alloys have a high affinity for oxygen and thus will react with the oxygen present in the undeoxidized melt and lose their effectiveness.
[0085] To deoxidize copper alloys, it is known to add phosphorus as a deoxidizing agent in the form of phosphorus copper. Deoxidization improves in particular the flow properties of the melt. In addition to this, it prevents the alloyed sulfur from being burned by the oxygen in the melt. As already mentioned, an excessively high residual content of phosphorus during composite casting increases the risk of brittle phase formation (iron phosphide) in the bonding zone. The exact amount of addition can be calculated via a stoichiometric ratio based on the oxygen activity of the actual melt. However, the measurement of the activity of the alloy used is only possible with disposable measuring heads and is always accompanied by measurement uncertainties. For small melt volumes of a few hundred kg, such measurements are not economical. Furthermore, the loss of oxygen and hydrogen due to the measurement itself is a notable drawback.
[0086] The use of lithium in the copper alloys brings about several advantages. Lithium has a pronounced deoxidizing effect. The small residual oxygen content thus obtained prevents the alloying element sulfur, and other elements with an affinity for oxygen, from burning. In addition to removing oxygen, lithium also has the property of combining with hydrogen (LiH, LiOH). This allows the lithium additive to also reduce the hydrogen content in the melt. Together with its reaction partners, lithium forms a liquid slag above the melt and prevents further oxygen and hydrogen from penetrating into the melt. Furthermore, lithium has a grain-refining effect in itself, which ensures a fine distribution of sulfides in the hydrogen.
[0087] To produce the multilayer plain bearing element 1, in a first step a semi-finished product can be produced from at least two layers. For this purpose, in the simplest case, a copper-based alloy can be cast onto a particularly flat metal strip or onto a particularly flat metal sheet.
[0088] The metal strips or sheets form the supporting metal layer 3. For the case in which flat metal strips or sheets are used, these are further transformed in subsequent method steps into the respective multi-layer plain bearing element 1, as is known per se in the prior art.
[0089] As already mentioned above, the multilayer plain bearing element 1 can also have more than two layers. In such a case, the copper-based alloy can be cast onto the respective uppermost layer of the composite material with the supporting metal layer 3, or a further, in particular two-layer, composite material is first produced and then this two-layer composite material is bonded to the supporting metal layer 3 or to the composite material with the supporting metal layer 3, for example by roller cladding, optionally with a bonding foil arranged in between.
[0090] Casting the copper-based alloy onto a metal strip or sheet, or onto a layer of a composite material, can be done, for example, by horizontal belt casting.
[0091] However, it is also possible that the copper-based alloy is produced in a first step, for example by continuous casting or ingot casting, and that the hardened copper-based alloy is only subsequently bonded to at least one of the further layers of the multilayer plain bearing element 1, in particular to the supporting metal layer 3, for example by roller cladding.
[0092] According to alternative embodiments, the multi-layer plain bearing element 1 can be manufactured by centrifugal casting or by gravity casting.
[0093] Direct coating of components, such as connecting rod eyes, is also possible. Powder coating methods can also be used.
[0094] The copper-based alloy can also be applied onto the respective lower layer of the multi-layer plain bearing element 1 or component according to a sintering method.
[0095] The proportions of the components in the starting mixture used for the production of the sliding layer 9 are selected in accordance with the indications in Table 1.
[0096] The casting of the alloy from the melt is basically known to the person skilled in the art of plain bearings, so reference is made to the relevant prior art for parameters such as temperature etc. The casting of the alloy is preferably carried out under a protective gas atmosphere.
[0097] Cooling of the solidified melt is preferably by oil to a temperature of approximately 300° C. and then by water and / or air to at least approximately room temperature, however, other forms of cooling are also possible. It is also preferred that forced cooling of the alloy or composite material is performed after casting.
[0098] After a possible deformation, for example into a half-shell shape, and possibly a finishing process, for example fine boring, coating, etc., the multilayer plain bearing element 1 is completed. Such finishing processes are known to those skilled in the art of plain bearings, and reference is made to the relevant literature in this regard.
[0099] According to one embodiment of the method, the copper-based alloy is subjected to deformation, in particular rolling, after casting. A degree of deformation of up to 80%, in particular between 20% and 80%, is used.
[0100] After deformation, in particular after rolling, the copper-based alloy can be subjected to a heat treatment. The heat treatment can be carried out at a temperature between about 200° C. and 700° C. The heat treatment can be carried out in a reducing atmosphere, for example under forming gas. Furthermore, the heat treatment can be carried out for a time period ranging from 2 hours to 20 hours. Due to the fine iron phosphide particles present in layer 4, no significant grain coarsening occurs during the heat treatment.
[0101] In addition to forming the further layer 4 as sliding layer 9, the further layer can also form another layer in the multilayer plain bearing element 1, for example a bearing metal layer arranged between the sliding layer and the supporting metal layer, or a run-in layer arranged on the sliding layer.
[0102] Some of the tests performed are reproduced below.
[0103] Generally speaking, the compositions for the copper-base alloys shown in Table 2 were prepared according to the following method.
[0104] A copper-based alloy was cast by belt casting onto a supporting metal layer 3 consisting of steel with dimensions 220 mm wide and 4 mm thick. The preheated steel had a temperature of 1070° C. and a speed of 2.5 m / min. A casting alloy having a temperature of about 1130° C. is cast onto the steel. The steel is cooled from below by oil cooling to about 350° C. and then further cooled with water, so that the casting alloy solidifies together. Such a composite was subjected to a thickness reduction of 40% by rolling. The material was then heat treated at 525° C. for 7 hours under a protective gas atmosphere and then deformed into a half-shell shape.
[0105] Depending on the alloy composition, the heat treatment of the material can be carried out, for example, at 450° C., in particular at 500° C. for 10 hours or at 630° C., in particular at 610° C. for 6 hours.
[0106] This results in a two-layer plain bearing element in the form of a half shell, in which the layer thickness of the sliding layer 9 is less than 1 mm.
[0107] For the avoidance of doubt, with respect to Table 2 below, it should be understood that all the indications regarding the composition are in weight percent, with copper forming the balance to 100% by weight in each case. Metallic, normal impurities resulting from production are not specifically indicated. This is merely an example within the ranges of amounts of the individual alloy components reproduced in Table 1. If no examples are assigned to the entire ranges shown in Table 1 for individual components or elements of the copper-based alloy, this means that there is no restriction to the item-by-item proportions reproduced in Table 2 for such elements. The quantitative indications for the elements shown in Table 2 are the quantitative indications used to produce the copper-based alloy.
[0108] For alloys having alloying elements of the second group, only two "base alloys" were always used, however, this does not mean that the addition of such elements is limited to the stated compositions of the "base alloys".
[0109] Furthermore, only one alloying element of the second group of the "base alloy" was always added in each case, but it goes without saying that within the scope of the invention compositions having two or more such alloying elements of the second group are also possible.
[0110] [Table 2-1] [Table 2-2] [Table 2-3] [Table 2-4] [Table 2-5] [Table 2-6] [Table 2-7]
[0111] The seizure tendency of such copper-based alloys was determined according to a seizure tendency test. The seizure tendency test was carried out on all multilayer plain bearing elements 1 corresponding to the examples in table 2. The measured values were standardized against a multilayer plain bearing element of the known alloy CuPb22Sn. Such alloys were defined with a seizure load of 100%. In comparison, the alloys shown in table 2 had values of 70% to 105%, which are not only very good values considering that they are lead-free, but also superior to leaded alloys.
[0112] In further tests, it was found that by adding boron, the hardness of the copper-based alloy can be adjusted within certain limits in cooperation with the cooling of the melt. For example, during quenching, a boron phase can be precipitated in the boundary region of the supporting metal layer 3 with the steel. This allows the change in the mechanical properties of the transition from the further layer 4 to the supporting metal layer 3 to be adjusted. By contrast, by cooling the melt more slowly compared to the cooling, the copper-based alloy can be adjusted to be softer. Alternatively or additionally, the precipitation of such a boron phase in the boundary region of the supporting metal layer 3 with the steel can also be influenced via the proportion of boron in the copper-based alloy. Of course, the boron phase can also be contained in the entire further layer.
[0113] By means of such an embodiment, by producing a copper-based alloy (casting it onto the layer arranged below said further layer 4), i.e. already during and by solidification of the copper-based alloy, a hardness gradient can be formed in said further layer 4 and further as a consequence in the multilayer plain bearing element 1. That is to say, no further post-treatment is necessary to form such a hardness gradient.
[0114] Due to the hardness gradient, the hardness decreases from the bonding zone, i.e. the boundary region of the supporting metal layer 3 with the steel or from the layer arranged underneath the further layer 4, towards the (radially) opposite surface of the further layer 4. This allows a low hardness to be present in the region of the sliding surface. A low hardness leads to a better compatibility of the further layer 4. On the other hand, the comparatively high hardness in the bonding zone makes it possible to avoid a highly variable hardness transition to the supporting metal layer 3 or to the layer arranged underneath the further layer 4. This makes it possible to better avoid or reduce mechanical stresses. This improves the durability or service life of the multilayer plain bearing element 1.
[0115] The concentration of boron phases increases i.e. from the (radially) inner surface of the further layer 4 towards the supporting metal layer 3 or the layer arranged below the further layer 4 of the multilayer plain bearing element 1. The concentration of boron phases is maximum in the bonding zone of the transition to the supporting metal layer 3 or the layer arranged below the further layer 4 of the multilayer plain bearing element 1.
[0116] In order to form a hardness gradient in the further layer 4, it is advantageous to apply a copper-based alloy by centrifugal casting onto the supporting metal layer 3 or onto a layer arranged below the further layer 4. However, other methods are also possible, for example belt casting.
[0117] The boron phase is primarily an iron-boron phase, however, other boron phases may form with the alloying elements of the copper-based alloy. The boron phase may generally occur within other regions of the copper-based alloy.
[0118] In the multilayer plain bearing element 1, the tribologically favorable layers can be further modified, for example by incorporating sulfide deposits in the top layer. The formation of such deposits allows boron to act in a supporting manner.
[0119] The invention further relates to a method for producing a multilayer plain bearing element 1, for which a composite material is produced having a supporting metal layer 3 and a further layer 4, in particular a sliding layer 9, and possibly an intermediate layer between said supporting metal layer 3 and said further layer 4. The further layer 4 is formed from a casting alloy consisting of a lead-free copper-based alloy, in which sulfide-containing precipitates 10 are contained. To produce a casting alloy, the copper-based alloy is preferably composed of 0.1% to 3% by weight of sulfur, 0.01% to 4% by weight of iron, 0% by weight, in particular 0.001% to 2% by weight of phosphorus, and a total of 0.1% to 49% by weight of at least one element from a first group consisting of zinc, tin, aluminum, manganese, nickel, silicon, chromium, indium, in which the proportion of zinc is 0% to 45% by weight, the proportion of tin is 0% to 40% by weight, the proportion of aluminum is 0% to 15% by weight, the proportion of manganese is 0% to 10% by weight, the proportion of nickel is 0% to 10% by weight and the proportion of silicon is 0% to 10% by weight. % to 10% by weight, a proportion of chromium of 0% to 2% by weight and a proportion of indium of 0% to 10% by weight, and at least one element from a second group consisting of silver, magnesium, indium, cobalt, titanium, zirconium, arsenic, lithium, yttrium, calcium, vanadium, molybdenum, tungsten, antimony, selenium, tellurium, bismuth, niobium, palladium, each in a proportion of 0% to 1.5% by weight, the total proportion of the elements of the second group being 0% to 2% by weight. The remainder to 100% by weight is made up of copper and impurities originating from the production of the elements.
[0120] To produce the casting alloy, the further quantities listed in Table 1 above may also be used.
[0121] The examples show or describe possible embodiments, whereby it should be noted that various combinations of the individual embodiments with one another are also possible.
[0122] Finally, it should be noted that, for the sake of clarity, the multilayer plain bearing element 1 or the structure of said further layer 4 is not necessarily shown to scale. The present disclosure also includes the following aspects. [Aspect 1] A multi-layer plain bearing element (1) made of a composite material, which has a supporting metal layer (3), a further layer (4), in particular a sliding layer (9), and possibly an intermediate layer between the supporting metal layer (3) and the further layer (4), the further layer (4) being formed from a lead-free copper-based casting alloy, in which sulfide-containing precipitates (10) are contained, the copper-based alloy comprises 0.1% to 3% by weight of sulfur, 0.01% to 4% by weight of iron, 0% by weight, in particular 0.001% to 2% by weight of phosphorus, and at least one element from a first group consisting of zinc, tin, aluminum, manganese, nickel, silicon, chromium, indium, in a total amount of 0.1% to 49% by weight, wherein the proportion of zinc is 0% to 45% by weight, the proportion of tin is 0% to 40% by weight, the proportion of aluminum is 0% to 15% by weight, the proportion of manganese is 0% to 10% by weight, the proportion of nickel is 0% to 10% by weight, the proportion of silicon is 0% to 10% by weight, the proportion of chromium is 0% to 2% by weight and the proportion of indium is 0% to 10% by weight, At least one element from a second group consisting of silver, magnesium, indium, cobalt, titanium, zirconium, arsenic, lithium, yttrium, calcium, vanadium, molybdenum, tungsten, antimony, selenium, tellurium, bismuth, niobium, and palladium, each of which is present in a proportion between 0% and 1.5% by weight, and the total proportion of the elements from said second group is between 0% and 2% by weight; and the remainder up to 100% by weight is made up of copper and impurities originating from the production of the element (1). [Aspect 2] 2. The multilayer plain bearing element (1) according to embodiment 1, characterized in that the copper-based alloy of the further layer (4) contains zinc or tin. [Aspect 3] 3. The multilayer plain bearing element (1) according to aspect 1 or 2, characterized in that the total proportion of elements from the first group consisting of zinc, tin, aluminum, manganese, nickel, silicon and chromium is between 0.5% and 15% by weight. Aspect 4 4. The multilayer plain bearing element (1) according to any one of the preceding claims, characterized in that the copper-based alloy of the further layer (4) contains 0.01% to 5% by weight of zinc. Aspect 5 5. The multilayer plain bearing element (1) according to any one of the preceding claims, characterized in that the copper-based alloy of the further layer (4) contains 0.01% to 10% by weight of tin. Aspect 6 6. The multilayer plain bearing element (1) according to any one of the preceding aspects, characterized in that the copper-based alloy of the further layer (4) contains 0.01% to 7.5% by weight of aluminum. Aspect 7 7. The multilayer plain bearing element (1) according to any one of the preceding aspects, characterized in that the copper-based alloy of the further layer (4) contains 0.01% to 5% by weight of manganese. Aspect 8 8. The multilayer plain bearing element (1) according to any one of the preceding aspects, characterized in that the copper-based alloy of the further layer (4) contains 0.01% to 5% by weight, in particular 0.01% to 2% by weight, of nickel. Aspect 9 9. The multilayer plain bearing element (1) according to any one of the preceding claims, characterized in that the copper-based alloy of the further layer (4) contains 0.01% to 7% by weight, in particular 0.01% to 3% by weight, of silicon. Aspect 10 10. The multilayer plain bearing element (1) according to any one of the preceding claims, characterized in that the copper-based alloy of the further layer (4) contains 0.01% to 1.5% by weight, in particular 0.01% to 1% by weight, of chromium. Aspect 11 11. The multilayer plain bearing element (1) according to any one of the preceding aspects, characterized in that the copper-based alloy of the further layer (4) contains 0.3% to 0.8% by weight of sulfur. Aspect 12 12. The multilayer plain bearing element (1) according to any one of the preceding aspects, characterized in that the copper-based alloy of the further layer (4) contains 0.01% to 0.1% by weight of phosphorus. Aspect 13 13. The multilayer plain bearing element (1) according to any one of the preceding aspects, characterized in that the copper-based alloy of the further layer (4) contains 0.3% to 1.5% by weight of iron. Aspect 14 14. The multilayer plain bearing element (1) according to any one of the preceding claims, characterized in that the copper-based alloy of the further layer (4) additionally contains 0.001% to 1.5% by weight, in particular 0.001% to 1% by weight, of boron. Aspect 15 15. The multilayer plain bearing element (1) according to any one of the preceding aspects, wherein the sulfide-containing precipitates (10) are present homogeneously distributed throughout the further layer (4). Aspect 16 15. The multilayer plain bearing element (1) according to any one of the preceding aspects, wherein the sulfide-containing precipitates (10) are formed only within the copper-based alloy sub-layer (12) of the further layer (4). Aspect 17 17. The multilayer plain bearing element (1) according to embodiment 16, wherein the partial layer (12) has a layer thickness (13) which is 5% to 85% of the total layer thickness (11) of the further layer (4). Aspect 18 18. The multilayer plain bearing element (1) according to any one of the preceding aspects, wherein the sulfide-containing precipitates consist of at least 50% by area of a mixture of copper sulfide and iron sulfide. Aspect 19 19. The multilayer plain bearing element (1) according to embodiment 18, wherein the proportion of copper sulfide in said mixture of copper sulfide and iron sulfide is at least 60% by area. [Explanation of symbols] [Explanation of symbols]
[0123] 1 Multilayer plain bearing element 2. Plain bearing element body 3 Support metal layer 4 layers 5 Bearing metal layer 6 Break-in layer 7 Plain bearing element 8 Plain bearing 9. Slip layer 10 Precipitate 11 Total thickness 12 partial layers 13 layer thickness 14 Surface 15 Particle size
Claims
1. A multilayer plain bearing element (1) made of a composite material, the composite material having a supporting metal layer (3) and a further layer (4), the further layer (4) being formed from a lead-free copper-based casting alloy, the copper-based alloy containing sulfide-containing precipitates (10), the copper-based alloy comprises 0.1% to 3% by weight of sulfur, 0.01% to 4% by weight of iron, 0% to 2% by weight of phosphorus, and at least one element from a first group consisting of zinc, tin, aluminum, manganese, nickel, silicon, chromium, indium, in a total amount of 0.1% to 49% by weight, wherein the proportion of zinc is 0% to 45% by weight, the proportion of tin is 0% to 40% by weight, the proportion of aluminum is 0% to 15% by weight, the proportion of manganese is 0% to 10% by weight, the proportion of nickel is 0% to 10% by weight, the proportion of silicon is 0.01% to 7% by weight, the proportion of chromium is 0% to 2% by weight, and the proportion of indium is 0% to 10% by weight, At least one element from a second group consisting of silver, magnesium, cobalt, titanium, zirconium, arsenic, lithium, yttrium, calcium, vanadium, molybdenum, tungsten, antimony, selenium, tellurium, bismuth, niobium, palladium, each of which is present in a proportion between 0% and 1.5% by weight, and the total proportion of the elements of said second group is between 0% and 2% by weight; and the remainder up to 100% by weight is made up of copper and impurities originating from the production of the element (1).
2. 2. A multilayer plain bearing element (1) according to claim 1, characterized in that the copper-based alloy of the further layer (4) contains zinc or tin.
3. 3. A multilayer plain bearing element (1) according to claim 1 or 2, characterized in that the total proportion of elements from the first group consisting of zinc, tin, aluminum, manganese, nickel, silicon and chromium is between 0.5% and 15% by weight.
4. A multilayer plain bearing element (1) according to any one of claims 1 to 3, characterised in that the copper-based alloy of the further layer (4) contains 0.01% to 5% by weight of zinc.
5. A multilayer plain bearing element (1) according to any one of claims 1 to 4, characterised in that the copper-based alloy of the further layer (4) contains 0.01% to 10% by weight of tin.
6. A multilayer plain bearing element (1) according to any one of the preceding claims, characterized in that the copper-based alloy of the further layer (4) contains 0.01% to 7.5% by weight of aluminium.
7. A multilayer plain bearing element (1) according to any one of the preceding claims, characterized in that the copper-based alloy of the further layer (4) contains 0.01% to 5% by weight of manganese.
8. A multilayer plain bearing element (1) according to any one of the preceding claims, characterized in that the copper-based alloy of the further layer (4) contains 0.01% to 5% by weight of nickel.
9. A multilayer plain bearing element (1) according to any one of the preceding claims, characterized in that the copper-based alloy of the further layer (4) contains 0.01% to 3% by weight of silicon.
10. A multilayer plain bearing element (1) according to any one of the preceding claims, characterized in that the copper-based alloy of the further layer (4) contains 0.01% to 1.5% by weight of chromium.
11. A multilayer plain bearing element (1) according to any one of the preceding claims, characterized in that the copper-based alloy of the further layer (4) contains 0.3% to 0.8% by weight of sulphur.
12. A multilayer plain bearing element (1) according to any one of the preceding claims, characterized in that the copper-based alloy of the further layer (4) contains 0.01% to 0.1% by weight of phosphorus.
13. A multilayer plain bearing element (1) according to any one of the preceding claims, characterized in that the copper-based alloy of the further layer (4) contains 0.3% to 1.5% by weight of iron.
14. A multilayer plain bearing element (1) according to any one of the preceding claims, characterized in that the copper-based alloy of the further layer (4) contains 0.001% to 1.5% by weight of boron.
15. 15. A multilayer plain bearing element (1) according to claim 1, wherein the sulfide-containing precipitates (10) are present homogeneously distributed within the entire further layer (4).
Citation Information
Patent Citations
component for media-carrying gas or water lines
DE202016101661U1
Slide member made of copper alloy
JP2014001448A
Lead-free copper alloy for casting with excellent mechanical properties
US20120082588A1
Low lead ingot
US20120121455A1
Copper alloy for sliding maerial which has excellent bearing properties
WO2007126006A1
